IMPLEMENTASI KEBIJAKAN GERAKAN LITERASI DIGITAL DI SMP N 3 COLOMADU - Alvisa Aulya Siregar; Nabila Wahyu Saputri; Atiqa Sabardila (Buletin Literasi Budaya Sekolah, 2023)
This research was conducted with a case study using qualitative research methods, which aims to gain deeper understanding and knowledge about implementation of the digital literacy movement policy at SMP N 3 Colomadu Research informant are school principals, literacy team coordinators, teachers, and students. Researchers collect data through interviews, observation, and document analysis. Observation is done by observing the interaction between the teacher and students in use digital technology in class. the researcher conducts document analysis, such as plans implementation of learning (RPP), student manuals, and meeting notes, to obtain information about the policies of the digital literacy movement at SMP Negeri 3 Colomadu. Data analysis by means of data reduction, data presentation, and data verification. The results of the study show that the implementation of the digital literacy movement policy at SMP N 3 Colomadu has been successful and effective. The determining factors for success are communication through coordination meetings, WhatsApp groups for classes and student guardians; resources are supported by the availability of human resources and financial, physical facilities, narrative instructions and technical implementation; policy implementers have a pretty good attitude and commitment; bureaucratic structure by forming a student literacy team.